Design and Development of a Mini Fresh Water Generator to Improve Freshwater Availability on Motor Sailing Vessels - Agus Prawoto; Antonius Edy Kristiyono; Imam Sutrisno (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2025)
Freshwater availability is a significant operational concern for motor sailing vessels, especially those navigating Indonesia’s extensive archipelagic regions with limited access to resupply points. Small vessels typically lack the space and energy resources required for conventional desalination systems, creating an urgent need for compact and efficient onboard water-making technology. This study aims to design, construct, and evaluate a miniaturized Fresh Water Generator (FWG) based on a small-scale thermal distillation process suitable for low-power marine applications. The research employed an applied engineering approach involving system design, 3D modeling, prototype fabrication, sensor integration, and performance testing under simulated ship conditions. The developed FWG incorporates an evaporator, passive air-cooled condenser, and Arduino-based monitoring system equipped with temperature, pH, and water-level sensors. Experimental results demonstrated a freshwater production rate of approximately 10 L/day, supported by stable thermal performance and an average distillate pH of 5.9. The system operated with low fuel consumption and maintained reliable automated monitoring throughout the trials. The findings indicate that the Mini FWG offers a practical, compact, and energy-efficient solution for small and medium-sized vessels, contributing to improved self-sufficiency and sustainability in maritime operations.